2020
DOI: 10.1002/agj2.20237
|View full text |Cite
|
Sign up to set email alerts
|

Number of samples for accurate visual estimation of mean herbage mass in Campos grasslands

Abstract: The number of samples is a major issue when estimating the mean herbage mass of grazed paddocks. The aim of this study was to assess the number of samples required for accurate visual estimation of mean herbage mass in relation to the herbage mass heterogeneity and size of paddocks. Data were collected across scales of space and time (273 sampling events) from paddocks on Campos grasslands in Uruguay, using the visual estimation technique. The mean herbage mass of the paddocks ranged from 270 to 6350 kg of dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The CVW values of 0.16–0.94 (Figure 5) is close to the range of 0.20–1.16 obtained on the same land area basis (0.5 × 0.5 m) in other pastures (Do Carmo et al, 2020; Dobos et al, 2021; Shiyomi et al, 1983, 1984). The maximum CVW would have been higher if the measurements had included occasions immediately after the rotational stocking periods in the paddock (Hirata, 2000a, 2000b, 2002; Hirata & Fukuyama, 1997; Ogura et al, 2002).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The CVW values of 0.16–0.94 (Figure 5) is close to the range of 0.20–1.16 obtained on the same land area basis (0.5 × 0.5 m) in other pastures (Do Carmo et al, 2020; Dobos et al, 2021; Shiyomi et al, 1983, 1984). The maximum CVW would have been higher if the measurements had included occasions immediately after the rotational stocking periods in the paddock (Hirata, 2000a, 2000b, 2002; Hirata & Fukuyama, 1997; Ogura et al, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…Interval (day) pastures (Do Carmo et al, 2020;Dobos et al, 2021;Shiyomi et al, 1983Shiyomi et al, , 1984. The maximum CV W would have been higher if the measurements had included occasions immediately after the rotational stocking periods in the paddock (Hirata, 2000a(Hirata, , 2000b(Hirata, , 2002Hirata & Fukuyama, 1997;Ogura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that adjusting the stocking rate and breeding strategy contributed to the promotion of grass height heterogeneity. This could be attributed to the fact that with taller grass and increased forage availability, cattle tend to selectively graze on the more palatable plants, leaving behind the less digestible, and thus less selected, plants, creating heterogeneity in grass height ( Do Carmo et al 2018 ;Tonn et al 2019 ). However, although grass height heterogeneity significantly increased after the management modifications, we did not observe changes in the abundance of grassland bird specialists.…”
Section: Discussionmentioning
confidence: 57%